RECONSTRUCTION OF MARRIAGE REGISTRATION POST DECISION OF THE MK RI No. 46/PUU-VIII/2010 Jo PERSPECTIVE OF SHARIA MAQOSHID & POSITIVE LAW - Sugianto & Agus Manurung (Yayasan Inspirasi Merah Putih Indonesia, 2024)
Indonesia in the 1945 Constitution of the Republic of Indonesia Article 1 paragraph 3